Morphological Analysis of Air Sacs in the Red-Winged Tinamou (Rhynchotus rufescens Temminck, 1815) - Viegas, Katia Aparecida da Silva (2024)
The red-winged tinamou (Rhynchotus rusfencens) is a bird belonging to the order Tinaniforme, family Tinamidae, present in South America, and due to its population decline is classified as LC (Least Concern) on the BirdLife International red list. This study aimed to evaluate the air sacs of this species, as anatomical studies of partridges are scarce. Ten cadaveric specimens were collected, and latex perfusion was used to solidify the material. The cervical air sac in the red-winged tinamou is smaller and has a more irregular conformation than other air sacs. The thoracic air sacs are symmetrical, and the cranial thoracic air sacs are smaller than the caudal ones. The abdominal air sacs are asymmetrical, and the largest, extending to the cloaca. Only one clavicular air sac was found, with three subdivisions: right, left, and medial. Additionally, right, and left extra-coelomatic portions were found, passing under the clavicle. In one of the animals, the latex-filled humeri were found, and in three other ribs, vertebral diverticula were present. There is no clear relationship between taxonomy and biology versus the quantity and conformation of air sacs, as different animals with taxonomic proximity present differences. This study enhances species-specific anatomical knowledge of the red-winged tinamou.